Interventional Techniques for the Ablation and Augmentation of Extraspinal Lytic Bone Metastases - Ahmed, Osman; Feinberg, Nicholas; Lea, William B. (Seminars in Interventional Radiology, 2019)
In addition to being a major source of cancer-related pain, metastatic osseous lesions are frequently at risk for pathologic fracture and its accompanying morbidity. While bony metastases are commonly thought of as occurring within the vertebral column, over 80% are found outside the spine. Percutaneous interventional treatment options for nonspinal metastases offer a broad array of minimally invasive, image-guided procedures that are rapidly effective, reduce the need for opioids, and often work in complementary fashion with adjunct treatments in radiation oncology, orthopaedic surgery, and/or medical oncology. This article presents an approach to assess extraspinal metastases, reviews available interventional techniques in use today, and offers example cases as an introductory primer to the thought process used for selecting the appropriate interventional treatment.
Keywords: interventional radiology; bone metastasis; osseous; malignancy; cementoplasty; ablation